2000
DOI: 10.1177/002215540004801109
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Ribosomal Transcription Factor UBF and AgNOR Staining Identify Apoptotic Events in Neoplastic Cells of Hodgkin's Disease and in Other Lymphoid Cells

Abstract: Ribosomal RNA synthesis is a key molecular process for understanding the mechanisms that drive cell proliferation. In this process, the upstream binding factor (UBF) is involved in regulating rDNA transcription at the nucleolus, together with RNA polymerase I. Recently, UBF was demonstrated to be a substrate for selective cleavage by specific proteases during apoptosis. Here we studied the expression of UBF in several cases of Hodgkin's disease (HD) by immunostaining and found it to be absent or clearly dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
4
11
0
Order By: Relevance
“…The findings of the present work are consistent with the data on camptothecin-induced of HeLa cells [5] and CD-95-induced apoptosis of Jurkat cells [4,8]. In these works the cleavage of UBF and the absence of B23 proteolysis were recorded, and total protein B23 content was unchanged even upon complete proteolysis of UBF [8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of the present work are consistent with the data on camptothecin-induced of HeLa cells [5] and CD-95-induced apoptosis of Jurkat cells [4,8]. In these works the cleavage of UBF and the absence of B23 proteolysis were recorded, and total protein B23 content was unchanged even upon complete proteolysis of UBF [8].…”
Section: Discussionsupporting
confidence: 92%
“…In some works [4,5,8] UBF was shown to be an early target of the apoptosis-induced proteolysis, which depends on both cell types and apoptosis inducers. We decided to assess the behavior of UBF during apoptosis of HeLa cells induced by TNF-α and emetine mixture.…”
Section: Changes In Ubf During Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…34 It was demonstrated that UBF moves out of nucleoli during apoptosis whereas other nucleolar protein such as B23 stay within these structures. 35 This behavior has been interpreted as the result of the cleavage of UBF by caspases and has established UBF as a target that is inactivated early during apoptosis. Furthermore, it was recently shown that during apoptosis UBF localized to fibrogranular threaded bodies whereas fibrillarin, B23 and C23 remained present in micronuclei.…”
Section: Discussionmentioning
confidence: 99%
“…1, e), which attests to its probable degradation. By this sign A3 antigen corresponded to nucleolar Ag-NOR proteins, UBF (RNA polymerase I cofactor), and nucleolin (protein involved in the regulation of rDNA transcription and rRNA maturation) [9,11]. Hence, the appearance of cells with abnormal location of A3 antigen in HeLa culture was associated with increased sensitivity of the culture to suppression of total protein synthesis with anisomycin.…”
Section: Resultsmentioning
confidence: 93%